Application of STEAM Learning to Enhance Students’ Critical Thinking Skills - Nur Lailatur Rohmah; Budi Jatmiko; Cahyo Febri Wijaksono (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to analyze the implementation of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning approach in enhancing students’ critical thinking skills. The urgency arises from the challenges of the Industrial Revolution 4.0 era in the 21st century, where technological advancement dominates all aspects of human life. However, Indonesia still struggles with low-quality human resources in the face of global competition. Educational reform through innovative learning approaches such as STEAM is therefore essential. Method: This research employed a qualitative approach with a literature study design. Data were collected from various academic sources, including books, journals, and credible scientific publications, which were then analyzed through thematic interpretation to identify the relevance and effectiveness of STEAM in fostering critical thinking abilities. Results: The findings reveal that the STEAM approach is practical in developing students’ critical thinking skills by encouraging integrative learning that connects scientific concepts with creativity, problem-solving, and real-world applications. Students engaged in STEAM-based learning show improved reasoning, analytical ability, and adaptability, which are crucial competencies in 21st-century education. Novelty: This study highlights the contribution of STEAM as not only a multidisciplinary learning model but also as an innovative educational reform strategy for Indonesia. By integrating art with science and technology, STEAM offers a holistic framework to prepare students for global challenges while simultaneously strengthening critical thinking as a core competency.